Determination of chlorine-containing compounds in disinfectants using ion-exchange chromatography - Lapina, Eugenia A. (2024)
Objectives. To develop a method for the determination of hypochlorite, chloride, chlorite, chlorate, and perchlorate ions in solution; to determine the limits of detection and quantitation for ClO−, Cl−, ClO2−, ClO3−, and ClO4 − ions; to evaluate the applicability of the developed method and its suitability for disinfectant analysis. Methods. Ionic chromatography using a conductometric detection system in isocratic elution mode. Results. The method developed for chromatographic determination of chlorine-containing ions can be used to quantify the content of hypochlorite, chloride, chlorite, chlorate, and perchlorate ions. In isocratic elution mode at 7.5 mM NaOH and a flow rate of 0.4 mL/min, the content of chlorine-containing ions can be determined with high sensitivity. The presented method does not require the use of expensive equipment for the ultrasensitive analysis of the studied compounds. Conclusions. A novel method for the simultaneous determination of hypochlorite, chloride, chlorite, chlorate, and perchlorate ions in case of their combined presence is proposed. The technique can be used to carry out routine control of the content of these disinfectant components during use, increasing their effectiveness at the same time as managing associated toxicological risks.